TERAPI TAWA DALAM MENURUNKAN KELUHAN EMESIS GRAVIDARUM - Neny Dwi Pebriasanty; Mira Triharini; Ni Ketut Alit (Universitas Airlangga, 2014)
Emesis Gravidarum or nausea and vomiting during pregnancy is a common complaint submitted by pregnant women in early pregnancy. Laughter therapy is a therapy that can cause effects happy, excited, comfortable, and can solve a variety of problems as well as psychological health. This therapy led to increased serotonin hormone that can suppress nausea and vomiting in pregnant women. The aim of this study was to analyze the effect of laughter therapy to decrease Emesis Gravidarum complaints in pregnant women. The study used Pre-Experimental as a design. Population is pregnant women having experience of emesis gravidarum in Rumah Sakit Marinir Gunung Sari Surabaya. 18 respondents are choosen by purposive sampling technique. The independent variable is laughter therapy and the dependent variable are reduction of nausea and vomiting. Data collected by questionnaires with level of significant alpha ≤ 0.05. The result shows p=0.002 (α <0.05). It indicates that there were a significant decrease in nausea and vomiting in pregnant women experiencing emesis gravidarum after getting laughter therapy. It can be concluded that there were significant level of decreasing nausea and vomiting by laughter therapy in pregnant women with emesis gravidarum. This therapy can be used continuously. Further studies are expected to be expanded sample and the presence of the control group.